Building confidence in quantitative systems pharmacology models: An engineer's guide to exploring the rationale in model design and development. (9th February 2017) - Timmis, J; Alden, K; Andrews, P; Clark, E; Nellis, A; Naylor, B; Coles, M; Kaye, P
Abstract : This tutorial promotes good practice for exploring the rationale of systems pharmacology models. A safety systems engineering inspired notation approach provides much needed rigor and transparency in development and application of models for therapeutic discovery and design of intervention strategies. Structured arguments over a model's development, underpinning biological knowledge, and analyses of model behaviors are constructed to determine the confidence that a model is fit for the purpose for which it will be applied.